Pregunta
upstudy study bank question image url

Given \( f(x)=5 x^{2}-4 \) and \( g(x)=6-\frac{1}{2} x^{2} \), find the following expressions. \( \begin{array}{llll}\text { (a) }(f \circ g)(4) & \text { (b) }(g \circ f)(2) & \text { (c) }(f \circ f)(1) & \text { (d) }(g \circ g)(0)\end{array} \) \( \begin{array}{ll}\text { (a) }(f \circ g)(4)=\square & \text { (Simplify your answer.) }\end{array} \)

Ask by Thornton Deleon. in the United States
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( (f \circ g)(4) = 16 \)

Solución

To solve the problem, we need to evaluate the compositions of the functions \( f \) and \( g \) at the specified points. Let's break it down step by step. ### Given Functions - \( f(x) = 5x^2 - 4 \) - \( g(x) = 6 - \frac{1}{2}x^2 \) ### (a) Calculate \( (f \circ g)(4) \) 1. **Evaluate \( g(4) \)**: \[ g(4) = 6 - \frac{1}{2}(4^2) = 6 - \frac{1}{2}(16) = 6 - 8 = -2 \] 2. **Now evaluate \( f(g(4)) = f(-2) \)**: \[ f(-2) = 5(-2)^2 - 4 = 5(4) - 4 = 20 - 4 = 16 \] Thus, \( (f \circ g)(4) = 16 \). ### (b) Calculate \( (g \circ f)(2) \) 1. **Evaluate \( f(2) \)**: \[ f(2) = 5(2^2) - 4 = 5(4) - 4 = 20 - 4 = 16 \] 2. **Now evaluate \( g(f(2)) = g(16) \)**: \[ g(16) = 6 - \frac{1}{2}(16^2) = 6 - \frac{1}{2}(256) = 6 - 128 = -122 \] Thus, \( (g \circ f)(2) = -122 \). ### (c) Calculate \( (f \circ f)(1) \) 1. **Evaluate \( f(1) \)**: \[ f(1) = 5(1^2) - 4 = 5(1) - 4 = 5 - 4 = 1 \] 2. **Now evaluate \( f(f(1)) = f(1) \)**: \[ f(1) = 1 \quad \text{(as calculated above)} \] Thus, \( (f \circ f)(1) = 1 \). ### (d) Calculate \( (g \circ g)(0) \) 1. **Evaluate \( g(0) \)**: \[ g(0) = 6 - \frac{1}{2}(0^2) = 6 - 0 = 6 \] 2. **Now evaluate \( g(g(0)) = g(6) \)**: \[ g(6) = 6 - \frac{1}{2}(6^2) = 6 - \frac{1}{2}(36) = 6 - 18 = -12 \] Thus, \( (g \circ g)(0) = -12 \). ### Summary of Results - \( (f \circ g)(4) = 16 \) - \( (g \circ f)(2) = -122 \) - \( (f \circ f)(1) = 1 \) - \( (g \circ g)(0) = -12 \) The final answers are: - (a) \( (f \circ g)(4) = 16 \) - (b) \( (g \circ f)(2) = -122 \) - (c) \( (f \circ f)(1) = 1 \) - (d) \( (g \circ g)(0) = -12 \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the expressions given, let's break down each function and apply the necessary transformations. First, we need to find \( (f \circ g)(4) \): 1. Calculate \( g(4) \): \[ g(4) = 6 - \frac{1}{2}(4^2) = 6 - \frac{1}{2}(16) = 6 - 8 = -2. \] 2. Now substitute this into \( f(x) \): \[ f(-2) = 5(-2)^2 - 4 = 5(4) - 4 = 20 - 4 = 16. \] So, \( (f \circ g)(4) = 16 \). Next, we find \( (g \circ f)(2) \): 1. Calculate \( f(2) \): \[ f(2) = 5(2^2) - 4 = 5(4) - 4 = 20 - 4 = 16. \] 2. Now substitute this into \( g(x) \): \[ g(16) = 6 - \frac{1}{2}(16^2) = 6 - \frac{1}{2}(256) = 6 - 128 = -122. \] So, \( (g \circ f)(2) = -122 \). Next, we find \( (f \circ f)(1) \): 1. Calculate \( f(1) \): \[ f(1) = 5(1^2) - 4 = 5(1) - 4 = 5 - 4 = 1. \] 2. Now substitute this back into \( f(x) \): \[ f(1) = 1 \text{ (already found)}. \] So, \( (f \circ f)(1) = 1 \). Finally, we find \( (g \circ g)(0) \): 1. Calculate \( g(0) \): \[ g(0) = 6 - \frac{1}{2}(0^2) = 6 - 0 = 6. \] 2. Now substitute this into \( g(x) \): \[ g(6) = 6 - \frac{1}{2}(6^2) = 6 - \frac{1}{2}(36) = 6 - 18 = -12. \] So, \( (g \circ g)(0) = -12 \). To summarize: \[ \begin{array}{ll} \text{(a)} & (f \circ g)(4) = 16,\\ \text{(b)} & (g \circ f)(2) = -122,\\ \text{(c)} & (f \circ f)(1) = 1,\\ \text{(d)} & (g \circ g)(0) = -12. \end{array} \]

preguntas relacionadas

Latest Pre Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad